Penerapan Standar Halal Pengelolaan Kantin Kampus UIN Sumatera Utara Medan - Napitupulu, Serli Lestari; Permata, Cahaya (AL-SULTHANIYAH, 2025)
The campus canteens within the UIN Sumatera Utara Medan environment have not yet obtained halal certification. The objective of this research is to examine how halal standards are implemented in the campus canteen of UIN Sumatera Utara and to identify the influencing factors. This research is an empirical legal study with a sociological and legal and statute approach. Data were collected through observation, interviews, and document studies. The data were then processed, analyzed, and described qualitatively. The findings of this research indicate that halal standards have been implemented in the campus canteen of UIN Sumatera Utara Medan, but not optimally, as halal certification has not yet been obtained, thereby leaving the halal assurance unconfirmed officially. Factors influencing this condition include the high level of trust from the academic community toward canteen operators, the lack of socialization and education from the authorities, and the absence of internal campus regulations regarding canteen certification.